Status and Distribution of Malayan Sun Bear (Helarctos malayanus) in North-eastern States, India - Chauhan, N. P. S.; , Lalthanpuia (Indian Forester, 2008)
Sun bear is the least known bear species and one of the most neglected large mammals in India. No information is available on its status, distribution, ecology and population threats from India. The surveys were conducted in the North-eastern region during 2002-2008 and information on status and distribution of Sun bear was collected in well designed questionnaire formats. In Arunachal Pradesh, direct and indirect evidences of Sun bear confirmed its presence in Namdapha Tiger Reserve and Murlen National Park and probability of its occurrence is shown in few protected areas. They are also present in Fakim WLS and Intanki WLS in Nagaland. In Mizoram, Sun bears occur in many protected areas including Dampa Tiger Reserve. Presence of Sun bears has been confirmed in the Chandel and Ukhrul districts of Manipur, but it showed patchy distribution. The paper presents its legal status and discusses conservation problems like population threats, habitat threats and human-bear interactions. Recommendations for conservation and management of Sun bear have also been made.